Catalytic application of polyoxovanadates in the selective oxidation of organic molecules - Jie Li; Di Zhang; Yingnan Chi; Changwen Hu (Polyoxometalates, 2022)
The structural synthesis and catalytic application of polyoxovanadates (POVs), an important subfamily of polyoxometalates (POMs), have attracted significant attention, owing to their rich coordination chemistry and splendid redox properties. In this review, the advances in the past 10 years in the oxidative transformations catalyzed using all-inorganic POVs, organ functionalized POVs, and POV-based inorganic–organic hybrids have been summarized and are discussed in detail. In particular, we focus on the selective oxidation of organic molecules, including alkanes, alkenes, alcohols, sulfides, sulfur-mustard simulants, and organic dyes. For most oxidative transformations, the active V-peroxo species generated in the presence of hydrogen peroxide or tert-butyl hydroperoxide account for enhanced catalytic activities. In addition, the challenges and prospects in the development of POM-based catalysts are addressed.